Epidemiology and Clinical Outcomes of Patients with Carbapenem-Resistant Klebsiella pneumoniae Bacteriuria - Qureshi, Zubair A. (American Society for Microbiology, 2014)
Carbapenem-resistant Klebsiella pneumoniae (CRKP) bacteriuria is a frequently encountered clinical condition, but its clinical impact is unknown. We conducted a retrospective cohort study to define the epidemiology and outcomes for patients with CRKP bacteriuria. Patients with positive urine cultures for CRKP were classified as having asymptomatic bacteriuria (ASB) or symptomatic urinary tract infection (UTI). Among 105 patients with CRKP bacteriuria, 80% (84/105 patients) and 20% (21/105 patients) had ASB and UTI, respectively. Older age (P = 0.002) and higher Charlson's comorbidity index scores (P = 0.001) were associated with ASB. The median duration of hospitalization prior to CRKP bacteriuria was significantly longer for patients with ASB versus UTI (8.5 versus 2 days; P = 0.05). In multivariate analysis, male sex (odds ratio [OR], 4.69 [95% confidence interval (CI), 1.44 to 15.26]; P = 0.01), solid-organ transplantation (OR, 4.50 [95% CI, 1.39 to 14.52]; P = 0.01), and neurogenic bladder (OR, 18.62 [95% CI, 1.75 to 197.52]; P = 0.01) were independently associated with UTI. Ten percent (8/84) of the patients with ASB received antimicrobial therapy. The treatment success rate for patients with UTIs was 90% (19/21 patients), including all patients who received doxycycline (n = 9). The overall 30-day mortality rate was 6% (6/105 patients); the deaths were unrelated to CRKP infections. Secondary CRKP infections, including UTIs, were notably absent among patients with ASB who were followed for 90 days. In conclusion, identification of CRKP in the urine was most commonly associated with ASB and did not lead to subsequent infections or death among asymptomatic patients. Factors associated with UTIs included male sex, solid-organ transplantation, and neurogenic bladder. Doxycycline may be an effective therapy for CRKP UTIs.